Impact of the 2019 volleyball proliga event on audience satisfaction and loyalty - Faisal S Sandrima; Yudik Prasetyo; Ali Algifari (Journal Sport Area, 2021)
The quality of service and the performance of the management team in a sporting event is thought to be able to influence audience satisfaction, so that these two things become important factors in the success of organizing sports matches. The purpose of this study was to determine and describe the impact of organizing sporting events on audience satisfaction and loyalty based on the quality of service and performance of the organizing committee in managing sports events. The study used a descriptive approach with qualitative and quantitative methods. 64 spectators were randomly selected from all the spectators who attended the volleyball proliga sport event held at GOR Amongrogo, Yogyakarta City. Data collection techniques uses a questionnaire. The data analysis technique used PLS - SEM. The results of the study found that there was an influence of service quality and performance of the match management team on audience satisfaction and loyalty. These results indicate that the indicators of the implementation of sports activities are measured by the satisfaction and loyalty level of the audience following the match with the service quality and management of the organizers as influencing factors.